Ethno-veterinary Herbal Medicines of Dwarahat Area of Central Himalayas - Tiwari, Dolly; Pande, P. C.; Tiwari, Lalit (Indian Forester, 2007)
The present paper deals with the utilization of plants and plant products in relation to the ethnoveterinary medicines of Dwarahat area of Uttarakhand Himalayas. Ethno-veterinary survey was conducted during 2003 and information on medicinal plants and their mode of therapeutic uses, local names were gathered from the villagers and experienced people. The aim of the present study is to document the traditional veterinary medicinal information against the diseases and disorders. Many of traditional practices and treatments are very unique and effective.